Hydrophobic structural modification of chitosan and its impact on nanoparticle synthesis – A physicochemical study. (1st October 2017) - Jothimani, B.; Sureshkumar, S.; Venkatachalapathy, B.
Highlights: N-(Thiophene-2-acetyl)chitosan was synthesized with a DS of 0.96 directly. The substitution makes the molecule easily processable to get nanoparticles. Chitin which is a naturally available fully acylated polymer, under similar conditions produced micro particles. Abstract: Chitin is a naturally occurring fully N-acylated biopolymer which cannot be converted into nanomaterial easily due to its inherent rigidity and chemical inertness. These properties limit the utility of chitin in nanomaterial-based applications. Therefore, our aim in the present work was, to prepare chitin like fully N-acylated derivatives with a hydrophobic moiety and study the impact on nanoparticles synthesis. We report such a fully substituted derivative, N-(Thiophene-2-acetyl)chitosan, its characterization and physicochemical studies of the nanoparticles synthesized. The study confirms that the hydrophobic structural modification of chitosan improves the processability of the material and defines the nanoparticles synthesis. This kind of organic nanoparticles, stable under wide pH range due to amine group protection of chitosan, can be used as nano- reinforcement material to enhance the properties of various composites.